OC-012 THE COMBINATION OF THE THREE MODIFICATIONS OF THE COMPONENT SEPARATION TECHNIQUE IN THE MANAGEMENT OF COMPLEX SUBCOSTAL WALL DEFECT. (13th October 2022) - Zuvela, M; Galun, D; Bogdanovic, A; Loncar, Z; Zivanovic, M; Zuvela, M; Zuvela, M
Abstract: Aim: To present a concept combining three modifications of the component separation technique (CST) in one procedure as an original solution for the management of complex subcostal abdominal wall defect. Material and Methods: Between January 2010 and January 2022, seven patients with complex subcostal hernia defects compromised by infection, radiation, or chemotherapy underwent surgery in which three modifications of CST were combined into one procedure. Major complex subcostal hernia was defined by either width or length of the defect being greater than 10 cm. The following were the stages of the operative technique: (a) the "method of wide myofascial release" at the side of the hernia defect; (b) "openbook variation" of the component separation technique at the opposite side of the hernia defect; (c) a modified component separation technique for closure of midline abdominal wall hernias in the presence of enterostomies; (d) suturing of the myofascial flaps to each other to cover the defect; and (e) repair augmentation with an absorbable mesh in the onlay position. Results: The median (range) length and width of the complex subcostal hernias were 15 cm (10–19) and 15 cm (8–24), respectively. The overall morbidity rate was 57.1% (wound infection, seroma and skin necrosis). There was no hernia recurrence during the median follow-up time of 19 (range 3–84) months. Conclusion: The operative technique integrating three modifications of CST in one procedure with onlay absorbable mesh reinforcement is a feasible solution for the management of complex subcostal abdominal wall defect.